2013
DOI: 10.21273/hortsci.48.7.875
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Benzyladenine and Dikegulac Sodium Application Affects Branching of Liners and Finished Herbaceous Perennial Plants

Abstract: Foliar spray applications of plant growth regulators (PGRs) benzyladenine (BA) and dikegulac sodium (DS) on herbaceous perennial liners and transplants were evaluated to determine effects on branching and quality. PGRs were applied three times (main plot): liner (24 h after removal from mist), post-transplant (5 to 7 days after transplant), or both (applications at liner and post-transplant). PGRs (subplots) were applied at concentrations of 400, 800, or 1600 mg·L−1 DS; 600 mg·L Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…An increase in DS concentration or pinch number resulted in a reduction in GI (Table 1). This result was in agreement with Grossman et al (2013), who reported two applications of DS at 1600 ppm reduced plant growth in all of the crops studied. Growth index also decreased as BA concentration increased up to the 1250 ppm (Table 1).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…An increase in DS concentration or pinch number resulted in a reduction in GI (Table 1). This result was in agreement with Grossman et al (2013), who reported two applications of DS at 1600 ppm reduced plant growth in all of the crops studied. Growth index also decreased as BA concentration increased up to the 1250 ppm (Table 1).…”
Section: Resultssupporting
confidence: 93%
“…Reduction in leaf area of plants treated with 2400 ppm DS likely contributed to the decreased dry weight observed at the same DS concentration. An increase in shoot dry weight following BA application has been reported previously in 'Autumn Joy' sedum (Grossman et al, 2013).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations